The attitudes and actions of others: Tutelage and Sutherland's theory of differential association - McCarthy, William (The British journal of criminology, 1996)
Contemporary studies of Sutherland's differential association theory argue that people learn about crime predominantly or exclusively through exposure to attitudes and motives that legitimize such behaviours. I suggest that Sutherland's writings demonstrate an equal concern with more direct exposure to crime; that is, with tutelage in criminal methods. I test this interpretation with models of drug selling and theft among a sample of homeless youths. In both cases, models that include deviant associations, attitudes, and desires improve with the addition of a measure of tutelage. Disregarding the role of tutelage may, therefore, mis-specify the differential association process and encourage misinterpretations of findings that correspond with Sutherland's theory